1998
DOI: 10.1128/jcm.36.1.139-147.1998
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Phylogenetically Related Slowly Growing Mycobacteria Based on 16S-23S rRNA Gene Internal Transcribed Spacer Sequences

Abstract: Interspecific polymorphisms of the 16S rRNA gene (rDNA) are widely used for species identification of mycobacteria. 16S rDNA sequences, however, do not vary greatly within a species, and they are either indistinguishable in some species, for example, in Mycobacterium kansasii and M. gastri, or highly similar, for example, in M. malmoense and M. szulgai. We determined 16S-23S rDNA internal transcribed spacer (ITS) sequences of 60 strains in the genus Mycobacterium representing 13 species (M. avium, M. conspicuu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
138
0
5

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 317 publications
(157 citation statements)
references
References 41 publications
8
138
0
5
Order By: Relevance
“…The relationships between ITS sequences from slow-growing Mycobacterium spp. showed only partial agreement with those based on SSU rDNA sequences (Roth et al, 1998), whereas a similar analysis for the genus Bifidobacterium showed much better agreement (Leblond-Bourget et al, 1996).…”
Section: Discussionmentioning
confidence: 71%
“…The relationships between ITS sequences from slow-growing Mycobacterium spp. showed only partial agreement with those based on SSU rDNA sequences (Roth et al, 1998), whereas a similar analysis for the genus Bifidobacterium showed much better agreement (Leblond-Bourget et al, 1996).…”
Section: Discussionmentioning
confidence: 71%
“…Several methods based on molecular biological techniques have been reported. The sequences that have been reported include hsp65, 16S rRNA gene, and ITS (Plikaytis et al, 1992;De Smet et al, 1995;Springer et al, 1996;Messer & Weigel, 1997;Roth et al, 1998;Brunello et al, 2001). Each gene has several advantages and disadvantages.…”
Section: Discussionmentioning
confidence: 99%
“…However, as certain groups of bacteria are known to present difficulties in identification by 16S rDNA sequencing, these bacteria should be excluded, and other housekeeping gene targets, e.g. rpoB, if available, are required [39][40][41][42]47,[50][51][52][53][54]153]. Regarding the interpretation of sequence data, this involves requirements concerning the length and quality of sequences, the choice of appropriate programs for analysis, and the final species assignment based on similarity search results.…”
Section: U S E F U L N E S S a N D L I M I T A T I O N S O F U S I N mentioning
confidence: 99%